2020
DOI: 10.1038/s41598-020-75231-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antitumor, pro-inflammatory, and pro-coagulant activities of Megalopyge opercularis J.E. Smith hemolymph and spine venom

Abstract: Contact with stinging spines venom from several Lepidoptera larvae may result in skin lesions. In Mexico, envenomation outbreaks caused by Megalopyge opercularis were reported between 2015 and 2016. The aim of this study was to identify the venomous caterpillars in Nuevo Leon, Mexico and evaluate several biological activities of their hemolymph (HEV) and spine setae (SSV) venoms. M. opercularis was identified by cytochrome oxidase subunit (COI) designed primers. HEV and SSV extracts cytotoxic activity was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…3 E , Right ). These data suggest that asp caterpillar venom possesses anticoagulant activity rather than procoagulant activity as previously reported ( 8 ). However, the insecticidal and anticoagulant activities observed occur at orders of magnitude higher concentration than the observed nociceptive effects.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…3 E , Right ). These data suggest that asp caterpillar venom possesses anticoagulant activity rather than procoagulant activity as previously reported ( 8 ). However, the insecticidal and anticoagulant activities observed occur at orders of magnitude higher concentration than the observed nociceptive effects.…”
Section: Resultssupporting
confidence: 89%
“…Asp caterpillar venoms display insecticidal and anticoagulant activities. Our finding that the venom is anticoagulant rather than procoagulant as previously reported ( 8 ) may reflect the use of a mechanical coagulometer in this study compared to absorbance-based methods used in the previous investigation. However, the insecticidal and anticoagulant activities observed occurred at moderately high concentrations (µg/g and µg/mL), i.e., six orders of magnitude higher than concentrations able to activate mammalian neurons (pg/mL).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…More than 300 complementary and alternative medicine treatments are currently used in Mexican folklore [ 17 ]. Some studies have shown that plants of the Anacardiaceae [ 41 ] , Papaveraceae [ 42 ] , Compositae [ 43 ] , Euphorbiaceae [ 44 ] , Acanthaceae [ 45 ], and Rutaceae [ 30 ] families have antioxidant, anti-inflammatory, antiparasitic, antimicrobial, and anticancer properties [ 46 , 47 , 48 ]. The search for new compounds with antitumor potential represents a priority in the pharmaceutical area due to new variants resistant to conventional antineoplasic drugs [ 10 ].…”
Section: Discussionmentioning
confidence: 99%